Effectiveness of growth promoters for the seagrass (Cymodocea nodosa) restoration - Marletta, Giuliana; Sacco, Domenico; Danovaro, Roberto; Bianchelli, Silvia (Frontiers in Plant Science, 2025)
Seagrass meadows are regressing due to the cumulative impacts that affect coastal ecosystems worldwide. Seagrass restoration has been repeatedly proposed to reverse this trend, although with contrasting results due to the difficulty in maintaining the transplanted rhizomes. Enhancing the vegetative propagation of the rhizome plantings (e.g., employing growth-promoters) could represent a reliable tool to increase the success of seagrass restoration. Here we tested the effects of physio-activators, as plant growth-promoting bacteria (PGPB), and synthetic hormones, as plant growth regulators (PGRs), on a seagrass species to assess their potential utilization to enhance restoration efficiency. We conducted two separate experiments in aquaria on Cymodocea nodosa fragments: in the first one, the fragments were exposed to PGRs for six weeks, while in the second experiment, the fragments were exposed to PGPB for four weeks. For each experiment (PGRs and PGPB), the formation of new roots and new leaves, the survivorship, and the trend of maximum leaf length were compared between the treated and control (not exposed to PGRs or PGPB) fragments. It was observed that only the PGPB had a significant effect on the fragments’ survivorship (90% in treated fragments vs. 25% in control ones) and contributed significantly to the formation of new leaves and roots of C. nodosa fragments. On the contrary, in the experiments with PGRs, no significant effects were observed between treated and control fragments, and both showed a survivorship of 100% at the end of the experiment. Our study showed that the application of growth-promoters (particularly PGPB) on fragments could increase their survival and the formation of new roots and leaves. Therefore, the use of PGPB on C. nodosa fragments can allow their re-employment in restoration interventions, without damaging the individuals of natural populations.